Outcomes of grafting intrasynovial tendons of the toes to the hands in 10 patients: a preliminary report. (June 2017) - Ohi, H.; Uchiyama, S.; Kanda, T.; Mukoda, M.; Hayashi, M.; Kato, H.
Ten patients had intrasynovial tendon grafting harvested from the toes for secondary flexor tendon reconstruction in nine fingers and one thumb in our institutes from 2009 to 2014. These patients were followed for a mean of 15 (range: 8–36) months. The ranges of total active motion of the proximal and distal interphalangeal joints of these nine fingers were 143° (range: 108–175°) and of the metacarpophalangeal and interphalangeal joints of one thumb were 110°. In conclusion, this technique is feasible and gives a good result when successful but with a high complication rate. Level of Evidence IV